Burnout, Boredom, and Gen Z Productivity: The Roles of Positive Cyberloafing and Digital Mindfulness - Ni Kadek Irma Dwi Lestari; Ida Bagus Teddy Prianthara (Business and Applied Management Journal, 2026)
This study examines the effects of burnout and boredom on Gen Z employee productivity by positioning positive cyberloafing and digital mindfulness as mediating mechanisms. A quantitative explanatory design was employed to test the proposed relationships. Data were collected from 178 Generation Z employees through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that boredom has a negative and significant effect on productivity, while burnout does not have a significant direct effect. Positive cyberloafing and digital mindfulness have positive and significant effects on productivity. The mediation results further indicate that both positive cyberloafing and digital mindfulness significantly mediate the relationships between burnout, boredom, and productivity. These findings suggest that Gen Z productivity in digital work environments is shaped not only by psychological strain but also by employees' ability to recover and regulate their digital behavior. This study contributes to digital workplace and human resource management literature by reframing cyberloafing as a conditional adaptive mechanism and positioning digital mindfulness as a personal resource for sustaining productivity. Practically, organizations should develop digital well-being policies that support structured digital micro-breaks, mindful technology use, and more meaningful work design.